EXPLORING THE USE OF ONLINE RESOURCES FOR ENGLISH LANGUAGE LEARNING: STUDENTS' PERSPECTIVES - Moh. Choirul Huda; Nugrananda Janattaka; Novan Aditya Prayoga (English Journal Literacy Utama, 2023)
The use of digital technology and the internet has changed how language education works. It gives learners many tools to get better at languages. Teachers and researchers need to understand what online language resources are available to help learners efficiently. This research's main goal is to look into the online resources that students use to learn English and see what students think about them. The data we collected shows that most students like using Language Learning Websites (LLW) to learn English. This shows that interactive websites are important for teaching languages in modern times. The finding that Language Learning Websites are the preferred choice among students aligns with the current trend of a diverse range of LLWs available. Dealing with the students’ perception, the findings shows that the students generally have a positive view of online resources for learning English. However, there are still some challenges to work on to make these online platforms better. Researchers and educators need to keep up with these changes to help language learners in the digital age